A PILOT MODEL FOR JAPANESE ONLINE TEACHING WITH JAPANESE TEACHERS – PROBLEMS AND SOLUTIONS - Binh, Than Thi My (VNU Journal of Foreign Studies; Vol 36 No 2, 2020)
This study analyzed the model of teaching and learning Japanese conversations online through the pilot program of the second-year students of VNU University of Foreign Languages and International Studies, with the purpose of clarifying the program’s usefulness as well as issues to be improved. The informants included 6 students and a Japanese teacher via “zoomchat”. The whole pilot program lasted 4 months with one session per week. Both the teacher and students demonstrated positive feedback about the program. 100% students expressed that online learning with the native teacher help them ‘Japanese proficiency and soft skills’, ‘conversational skills’, ‘Japanese pronunciation’, ‘understanding of Japanese culture’, amongst others. The teacher also talked of various benefits of online teaching in terms of ‘cost, venue and time’, and the possibility to connect learners from different countries around the world. Also, this online mode of teaching/learning bring the learners ‘closer to Japan’.